What modern chemists have done for domestic science - Worden, Edith (My University, 1906)
Introduction: The woman of today who would make her home a model of all it should be in point of beauty, cleanliness, healthfulness, and opportunities for ever larger development, must be the mistress of many sciences. If she would have her house constructed of proper materials and suitably located, and surrounded by the beauties of nature, she must know something of architecture and landscape gardening; for a pleasing interior the science of color and line harmony come into play. She must know physics and hydraulics that she may know that her house is properly plumbed, heated and ventilated. The science of economics enables her to watch intelligently the trend of business affairs and so plan wisely her own household affairs. The science of mathematics enables her to figure out her expenses - the cost of clothing and food - and thus use the family income to the best advantage. From physiology she learns the conditions of the body in health and disease, and from chemistry, the constituents of food, the effects of cookery on it, and the particular need each constituent subserves. Chemistry also teaches her the composition of the various cooking utensils she uses and the best way to take care of them; the mysteries of the fuel she burns and the ways of getting the greatest amount of heat from it; the effects of poisons, food adulterations an preservatives; the effects of various chemical substances used in the laundry upon her clothes; the composition of the water used for drinking and cooking; the dyeing of fabrics which are used as clothing, draperies and for fancy work.
Citation: Worden, Edith. What modern chemists have done for domestic science. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Domestic Science; Home Economics; Chemistry; Theses